Clinical and intravascular imaging outcomes at 1 and 2 years after implantation of absorb everolimus eluting bioresorbable vascular scaffolds in small vessels. Late lumen enlargement: does bioresorption matter with small vessel size? Insight from the ABSORB cohort B trial. Issue 2 (31st October 2012) - Diletti, Roberto; Farooq, Vasim; Girasis, Chrysafios; Bourantas, Christos; Onuma, Yoshinobu; Heo, Jung Ho; Gogas, Bill D; van Geuns, Robert-Jan; Regar, Evelyn; de Bruyne, Bernard; Dudek, Dariusz; Thuesen, Leif; et al.
Abstract : Background: The long-term results after second generation everolimus eluting bioresorbable vascular scaffold (Absorb BVS) placement in small vessels are unknown. Therefore, we investigated the impact of vessel size on long-term outcomes, after Absorb BVS implantation. Methods: In ABSORB Cohort B Trial, out of the total study population (101 patients), 45 patients were assigned to undergo 6-month and 2-year angiographic follow-up (Cohort B1) and 56 patients to have angiographic follow-up at 1-year (Cohort B2). The pre-reference vessel diameter (RVD) was <2.5 mm (small-vessel group) in 41 patients (41 lesions) and ≥2.5 mm (large-vessel group) in 60 patients (61 lesions). Outcomes were compared according to pre-RVD. Results: At 2-year angiographic follow-up no differences in late lumen loss (0.29±0.16 mm vs 0.25±0.22 mm, p=0.4391), and in-segment binary restenosis (5.3% vs 5.3% p=1.0000) were demonstrated between groups. In the small-vessel group, intravascular ultrasound analysis showed a significant increase in vessel area (12.25±3.47 mm 2 vs 13.09±3.38 mm 2 p=0.0015), scaffold area (5.76±0.96 mm 2 vs 6.41±1.30 mm 2 p=0.0008) and lumen area (5.71±0.98 mm 2 vs 6.20±1.27 mm 2 p=0.0155) between 6-months and 2-year follow-up. No differences in plaque composition were reported between groups at either time point. At 2-year clinical follow-up, no differences in ischaemia-driven major adverse cardiac events (7.3% vs 10.2%, p=0.7335), myocardial infarction (4.9% vs 1.7%, p=0.5662) or ischaemia-driven target lesion revascularisation (2.4% vs 8.5%, p=0.3962) were reported between small and large vessels. No deaths or scaffold thrombosis were observed. Conclusions: Similar clinical and angiographic outcomes at 2-year follow-up were reported in small and large vessel groups. A significant late lumen enlargement and positive vessel remodelling were observed in small vessels.